Antimicrobial effect of Zataria multiflora Boiss. essential oil on Escherichia coli O157:H7 during manufacture and ripening of white brined cheese - KH Mohammadi; G Karim; SH Hanifian; A Tarinejad; R Gasemnezhad (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2011)
Thyme (Zataria multiflora Boiss) cultivated in Iran is extensively used as flavoring agent in dairy products. Also it has antimicrobial effects on the pathogenic bacteria which cause some food borne diseases. The aim of this study was to evaluate the antimicrobial effect of this plant’s essential oil on Escherichia coli O157:H7 in white brined cheese, considering the organoleptic properties of cheese. The essential oil of Z. multiflora Boiss. was obtained by hydrodistillation and analyzed by GC/MS. Preliminary sensory tests were carried out to establish the upper level of the essential oil incorporation. At the end of storage time, evaluation of the sensory characteristics of the supplemented cheeses suggested that, Z. multiflora Boiss. essential oil’s concentrations more than 200 ppm in cheese milk had adverse effects on the taste and odor of cheeses. Therefore, further examinations were carried out with 0, 100, 150 and 200 ppm concentrations. The inhibitory effects of different concentrations of the Z. multiflora Boiss. essential oil on E. coli O157:H7 were determined by enumeration of the microorganism on selective media and comparing the bacterial counts in different groups. The inhibitory effect of Z. multiflora Boiss. essential oil at concentration of 200 ppm was higher compared to its lower concentrations and also compared to the control groups. No significant difference (P > 0.05) was observed between the pH values of control groups and treated samples. Incorporation of Z. multiflora Boiss. essential oil at concentration of 200 ppm into cheese milk had significant antibacterial activity (P